Grape peel (Syrah var.) jam as a polyphenol-enriched functional food ingredient - Amorim, Frederico Lopes; de Cerqueira Silva, Mariana Barros [UNESP]; Cirqueira, Marina Gonçalves; Oliveira, Roseane Santos; Machado, Bruna Aparecida Souza; Gomes, Raquel Gutierres; de Souza, Carolina Oliveira; Druzian, Janice Izabel; de Souza Ferreira, Ederlan; Umsza-Guez, Marcelo Andrés (Wiley, 2019)
In this study, we evaluated the effects of the storage time on the physicochemical properties, bioactive compound content, and antioxidant capacity of jam prepared from grape peel extract to explore its potential as a supplementary food and/or functional ingredient. The ethanolic extract from Syrah var. grape peel exhibited high bioactive compound concentrations and antioxidant activity. The jam stability (prepared with 8.9% of extract) at 14°C was evaluated at 0, 15, 30, 45, and 60 days. The jam was found to contain high concentrations of polyphenolic compounds (137.0 ± 3.2 mg of gallic acid equivalent/100 g), total flavonoids (128.5 ± 23.0 mg of equivalent/100 g), and total anthocyanins (92.5 ± 4.0 mg of cyanidin equivalent/100 g). However, a large reduction in the flavonoid (70%–90%), anthocyanin (29%–35%), and phenolic (23%–30%) content was observed during storage. The free radical-scavenging activity (DPPH − ), ferric reducing antioxidant power (FRAP), and β-carotene-linoleic acid assays revealed the great antioxidant potential of the jam prepared from grape peel extract, which exhibited significant levels of radical-neutralizing activity, especially as determined by the DPPH method with EC 50 values ranging from 2.3 ± 0.1 to 3.9 ± 0.1 µg/ml. High R 2 values (p > 0.90) were obtained for the correlation between the DPPH results and the concentrations of the compounds of interest. In summary, the high bioactive compound contents and antioxidant capacity of the jam produced from grape peel suggest that it may provide health benefits as a source of natural antioxidants upon incorporation to several food industry products.
Keywords: antioxidant potential; bioactive compounds; grape product; physicochemical properties; shelf life